Influence of uncorrected refractive error and unmet refractive error on visual impairment in a Brazilian population - Ferraz, Fabio H. [UNESP]; Corrente, José Eduardo [UNESP]; Opromolla, Paula [UNESP]; Schellini, Silvana Artioli [UNESP] (Biomed Central Ltd., 2014)
Background: The World Health Organization (WHO) definitions of blindness and visual impairment are widely based on best-corrected visual acuity excluding uncorrected refractive errors (URE) as a visual impairment cause. Recently, URE was included as a cause of visual impairment, thus emphasizing the burden of visual impairment due to refractive error (RE) worldwide is substantially higher. The purpose of the present study is to determine the reversal of visual impairment and blindness in the population correcting RE and possible associations between RE and individual characteristics.Methods: A cross-sectional study was conducted in nine counties of the western region of state of Sao Paulo, using systematic and random sampling of households between March 2004 and July 2005. Individuals aged more than 1 year old were included and were evaluated for demographic data, eye complaints, history, and eye exam, including no corrected visual acuity (NCVA), best corrected vision acuity (BCVA), automatic and manual refractive examination. The definition adopted for URE was applied to individuals with NCVA > 0.15 logMAR and BCVA <= 0.15 logMAR after refractive correction and unmet refractive error (UREN), individuals who had visual impairment or blindness (NCVA > 0.5 logMAR) and BCVA <= 0.5 logMAR after optical correction.Results: A total of 70.2% of subjects had normal NCVA. URE was detected in 13.8%. Prevalence of 4.6% of optically reversible low vision and 1.8% of blindness reversible by optical correction were found. UREN was detected in 6.5% of individuals, more frequently observed in women over the age of 50 and in higher RE carriers. Visual impairment related to eye diseases is not reversible with spectacles. Using multivariate analysis, associations between URE and UREN with regard to sex, age and RE was observed.Conclusion: RE is an important cause of reversible blindness and low vision in the Brazilian population.
Keywords: Blindness; Visual impairment; Spectacles; Refractive errors; URE; UREN